Covering substrate

By forming a characteristic coating on the conductive substrate, the problems of difficulty in controlling the thickness of the covering substrate and insufficient mass production in the prior art are solved, and new covering substrates for various fields are realized, reducing costs and expanding Substrate and shape options.

CN119317738APending Publication Date: 2025-01-14NITERRA CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380044412.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-05
Filing Date
2023-07-20
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

Existing cover substrates have difficulties in thickness control and insufficient mass production in applications in various fields, and the prior art has failed to provide efficient coating solutions that meet a variety of substrate shapes and complex shapes.

Method used

The coating thickness determined by X-ray photoelectron spectroscopy is above 1 nm and below 800 nm, the percentage of C (carbon) element is above 0.1 atm and below 20 atm, and the percentage of total element of metal elements and O (oxygen) is 70 atm. Amorphous film with a relative density of more than % and a relative density of more than 90%, and a coating is formed on the conductive substrate by electrodeposition method. Compounds containing C-H bonds, C=O bonds, and C-O bonds are used, and metal elements such as Al are used. , Ti, Mo, etc., combine halogen elements to improve adhesion and homogeneity of the coating.

Benefits of technology

Achieve new cover substrates for various fields and energy-generating, reducing costs, expanding substrate and shape options without heat treatment or post-light irradiation, ensuring the stability and adhesion of the coating .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119317738A_ABST
    Figure CN119317738A_ABST
Patent Text Reader

Abstract

Provided is a novel cover substrate that can be used in various fields and can be mass-produced. The covering base material (1) is obtained by covering a base material (5) with a film (3). The thickness of the coating film (3) is 1 nm or more and less than 800 nm. When the coating film (3) is measured by X-ray photoelectron spectroscopy, the elemental percentage of C (carbon) is 0.1 atm% or more but less than 20 atm%, and the total elemental percentage of metal elements and O (oxygen) is 70 atm% or more. The relative density of the coating film (3) is 90% or more. The coating film (3) is in an amorphous state.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to covering substrates. Background Art

[0002] Patent Documents 1 to 4 disclose a coated substrate having a metal oxide coating. In Patent Documents 1 to 4, a wet film forming method is used. On the other hand, in order to control the thickness in accordance with a complex substrate shape, a dry film forming method (dry process) is sometimes used.

[0003] Considering the application to various fields and mass productivity, the existing covering substrates are not necessarily sufficient, and the development of new covering substrates is eagerly desired.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2011-32521

[0007] Patent Document 2: Japanese Patent Application Publication No. 2009-147192

[0008] Patent Document 3: Japanese Patent Application Publication No. 2015-93821

[0009] Patent Document 4: Japanese Patent Application Laid-Open No. 9-202606 Summary of the invention

[0010] Problem that the invention aims to solve

[0011] The present disclosure is made in view of the above actual situation, and its purpose is to provide a novel covering substrate that can be used in various fields and can be mass-produced. The present disclosure can be implemented in the following manner.

[0012] Solutions for solving problems [1]

[0014] A covering substrate, which is formed by covering the substrate with a coating film,

[0015] The thickness of the coating is greater than 1 nm and less than 800 nm.

[0016] When the film is measured by X-ray photoelectron spectroscopy, the element percentage of C (carbon) is 0.1 atm% or more and less than 20 atm%, and the total element percentage of metal elements and O (oxygen) is 70 atm% or more.

[0017] The relative density of the aforementioned coating is 90% or more,

[0018] The aforementioned coating is amorphous. [2]

[0020] The covered substrate according to [1], wherein a portion of the substrate where the coating film is formed has conductivity. [3]

[0022] The coated substrate according to [1] or [2], wherein the coating film contains a compound having at least one structure of a CH bond, a C═O bond, and a CO bond. [4]

[0024] The coated substrate according to [1] or [2], wherein the element percentage of the halogen element in the coating film is 0.1 atm% or more when measured by X-ray photoelectron spectroscopy. [5]

[0026] The covered substrate according to [1] or [2], wherein the metal element is at least one selected from the group consisting of Al (aluminum), Ti (titanium), Mo (molybdenum), Cr (chromium), Mn (manganese), Fe (iron), Co (cobalt), Ni (nickel), Zr (zirconium), V (vanadium), W (tungsten), Ta (tantalum), Nb (niobium) and Sn (tin).

[0027] Effects of the Invention

[0028] According to the present disclosure, a novel covering substrate that can be used in various fields and can be mass-produced is provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 Schematic diagram of the film forming device.

[0030] Figure 2 This is an image of a cross section of the cover substrate in Example 1 observed by FIB-SEM.

[0031] Figure 3 Graph showing the relationship between electrodeposition time and deposition weight (deposition mass).

[0032] Figure 4 This is a graph showing the relationship between the number of samples produced and the concentration of aluminum element in the bath solution. DETAILED DESCRIPTION

[0033] The details of the disclosure are described below. It should be noted that in this specification, regarding the numerical range, the description using "-" includes the lower limit and the upper limit unless otherwise specified. For example, the so-called "10-20" description includes "10" as the lower limit and "20" as the upper limit. That is, "10-20" and "10 or more and 20 or less" have the same meaning. In addition, in this specification, the upper limit and lower limit of each numerical range can be arbitrarily combined.

[0034] 1. Covering substrate 1

[0035] The covered substrate 1 is formed by covering the substrate 5 with the coating 3. The thickness of the coating 3 is 1 nm or more and less than 800 nm. When the coating 3 is measured by X-ray photoelectron spectroscopy, the element percentage of C (carbon) is 0.1 atm% or more and less than 20 atm%, and the total element percentage of metal elements and O (oxygen) is 70 atm% or more. The relative density of the coating 3 is 90% or more. The coating 3 is amorphous.

[0036] (1) Base material 5

[0037] The substrate 5 is not particularly limited. In order to improve the adhesion of the coating 3 to the substrate 5, it is preferably composed of a material that at least the portion (region) of the substrate 5 covered by the coating 3 has conductivity and can become the negative electrode 7 (cathode). The portion of the substrate 5 covered by the coating 3 has conductivity and becomes the negative electrode 7 (cathode), so that the coating 3 can be easily formed at this portion by the manufacturing method described later.

[0038] The surface portion of the substrate 5 can be made of a material that has conductivity and can serve as the negative electrode 7. The entire substrate 5 can be made of a material that can serve as the negative electrode 7. As the material that can serve as the negative electrode 7, for example, iron alloys and carbon are suitable. Suitable examples of iron alloys include one or more selected from Fe-Ni-Cr alloys (stainless steel), Fe-Ni alloys (Permalloy), Fe-Si alloys (ferrosilicon), Fe-Si-Al alloys (FeSiAl alloys), Fe-Ni-Mo (superpermeable alloys), Fe-Co alloys (Permalloy), and Fe-CB alloys (amorphous).

[0039] (2) Lamination 3

[0040] (2.1) Thickness

[0041] From the viewpoint of reflecting the function according to the material of the coating 3, the thickness of the coating 3 is 1 nm or more, preferably 10 nm or more, and more preferably 50 nm or more. On the other hand, from the viewpoint of withstanding the stress generated in the coating 3 and ensuring the close adhesion with the substrate 5, it is less than 800 nm, preferably 500 nm or less, and more preferably 200 nm or less. From these viewpoints, the thickness of the coating 3 is 1 nm or more and less than 800 nm, preferably 10 nm or more and 500 nm or less, and more preferably 50 nm or more and 200 nm or less. It should be noted that when the thickness of the coating 3 is not constant, the thickness condition is satisfied as long as the thickness of at least a part of the coating 3 is within the above range. The thickness of the coating 3 can be obtained by FIB-SEM observation.

[0042] (2.2) Element percentage of C (carbon)

[0043] The element percentage of C (carbon) when measuring the coating 3 by X-ray photoelectron spectroscopy (XPS method) is 0.1 atm% or more, preferably 0.5 atm% or more, and more preferably 1 atm% or more, from the viewpoint of suppressing grain growth in the coating 3 and stabilizing the properties of the coating 3. On the other hand, from the viewpoint of making the coating 3 fully function as an inorganic coating, it is less than 20 atm%, preferably 15 atm% or less, and more preferably 10 atm% or less. From these viewpoints, the element percentage of C (carbon) is 0.1 atm% or more and less than 20 atm%, preferably 0.5 atm% or more and 15 atm% or less, and more preferably 1 atm% or more and 10 atm% or less. It should be noted that when the composition of the coating 3 is not constant, the condition of the element percentage of C (carbon) is satisfied as long as the composition of at least a part of the coating 3 is within the above range.

[0044] Composition analysis based on X-ray photoelectron spectroscopy can be performed using an X-ray photoelectron spectroscopy analyzer. As measurement conditions, the X-ray source is aluminum metal Kα rays, the beam diameter is 100 μm, and the X-ray incident angle relative to the surface to be analyzed is 45° to scan the cross section, thereby enabling measurement.

[0045] (2.3) Total element percentage of metal elements and O (oxygen)

[0046] The total element percentage of the metal element and O (oxygen) when the coating 3 is measured by X-ray photoelectron spectroscopy (XPS method) is 70 atm% or more, preferably 80 atm% or more, and more preferably 90 atm% or more from the viewpoint of making the coating 3 fully function as an inorganic coating. It should be noted that the upper limit of the total element percentage of the metal element and O (oxygen) is the value obtained by subtracting the element percentage (atm%) of C (carbon) from 100 atm%. In the case where the composition of the coating 3 is not constant, the condition of the total element percentage of the metal element and O (oxygen) is satisfied as long as the composition of at least a part of the coating 3 is within the above range.

[0047] (2.4) Relative density of coating 3

[0048] From the viewpoint of fully exerting the function of the coating 3, the relative density of the coating 3 is 90% or more, preferably 95% or more, and more preferably 98% or more. The relative density of the coating 3 may be 100%.

[0049] The relative density of the coating 3 is calculated according to the following method. A cross-sectional TEM image is obtained by cutting along the film thickness direction of the coating 3. The area of ​​the pores is measured in a field of view of 300 nm in length and 1000 nm in width. The relative density (%) is calculated by the following formula (1). The average value of the relative density of 10 fields of view is the relative density of the coating 3. It should be noted that when the thickness of the coating 3 is less than 300 nm in length, the measurement is performed in a field of view that matches the thickness of the coating 3.

[0050] Relative density (%) = {(S1-S2) / S1} × 100 (1)

[0051] (Where S1 is the area of ​​the field of view (nm) with a vertical dimension of 300 nm and a horizontal dimension of 1000 nm 2 ), S2 is the total area of ​​pores in the field of view of 300 nm in length and 1000 nm in width (nm 2 ))

[0052] (2.5) Amorphous

[0053] The coating 3 is amorphous. The amorphous state can be confirmed by TEM images. Since the coating 3 is amorphous, it is expected to exhibit unique functions such as no crystal grains falling off and smooth outermost surface due to uniform film growth.

[0054] (2.6) Compounds having at least one of a CH bond, a C═O bond, and a CO bond

[0055] The coating 3 preferably contains a compound having at least one structure of a CH bond, a C=O bond, and a CO bond. The compound having at least one structure of a CH, C=O, and CO bond volatilizes at a lower temperature than simple C (carbon) and induces shrinkage of the coating 3, so it is estimated that the density of the coating 3 is improved.

[0056] Furthermore, the compound having at least one structure of a CH bond, a C═O bond, and a CO bond remains in the coating 3 , and it is presumed that the flexibility of the coating 3 is maintained and the adhesion of the coating 3 to the substrate 5 is also improved.

[0057] (2.7) Halogen elements

[0058] When the coating 3 is measured by X-ray photoelectron spectroscopy, the element percentage of the halogen element is preferably 0.1 atm% or more, more preferably 0.3 atm% or more, and further preferably 0.5 atm% or more. The upper limit of the element percentage of the halogen element is 3 atm% or less.

[0059] By containing a trace amount of halogen elements in the coating 3 , the oxide film present on the surface S of the substrate 5 is removed by the action of the halogen elements, resulting in a structure in which the coating 3 and the substrate 5 are in direct contact, and it is considered that the adhesion between the substrate 5 and the coating 3 is ensured.

[0060] (2.8) Metal elements

[0061] The metal element is not particularly limited. From the viewpoint of making the coating 3 function as a high-quality protective film of the substrate 5, the metal element is preferably at least one selected from the group consisting of Al (aluminum), Ti (titanium), Mo (molybdenum), Cr (chromium), Mn (manganese), Fe (iron), Co (cobalt), Ni (nickel), Zr (zirconium), V (vanadium), W (tungsten), Ta (tantalum), Nb (niobium) and Sn (tin).

[0062] 2. Method for manufacturing the covering substrate 1

[0063] The method for producing the cover substrate 1 of the present disclosure is not particularly limited.

[0064] The preferred manufacturing method is described below. The preferred manufacturing method is a manufacturing method for covering the substrate 1 using a bath 2 in which an organic solvent is used as a solvent. The water content of the bath 2 is less than 1% by mass, contains at least one or more metal elements, and contains at least one or more halogen elements. A voltage is applied in a state where the substrate 5 is immersed in the bath 2, thereby forming a coating 3 on the substrate 5 on the negative electrode 7 side (cathode side). In the manufacturing method disclosed in the present invention, by performing electrodeposition on the negative electrode 7 side, oxidation of the substrate 5 can be suppressed compared to performing electrodeposition on the positive electrode 6 side (anode side).

[0065] (1) Bath lotion 2

[0066] Bath 2 uses an organic solvent as a solvent.

[0067] (1.1) Water content

[0068] From the viewpoint of ensuring the homogeneity of the coating 3 and suppressing oxidation of the substrate 5, the water content of the bath liquid 2 is set to be less than 1% by mass. The water content is preferably less than 0.5% by mass, more preferably less than 0.1% by mass. The water content may be 0% by mass. The water content of the bath liquid 2 can be determined by GC-MS analysis.

[0069] (1.2) Metal elements

[0070] The bath 2 contains at least one or more metal elements. The metal element is not particularly limited. From the viewpoint of making the coating 3 function as a high-quality protective film of the substrate 5, it is preferred that the metal element is at least one selected from the group consisting of Al (aluminum), Ti (titanium), Mo (molybdenum), Cr (chromium), Mn (manganese), Fe (iron), Co (cobalt), Ni (nickel), Zr (zirconium), V (vanadium), W (tungsten), Ta (tantalum), Nb (niobium) and Sn (tin). In the manufacturing method disclosed in the present invention, the coating 3, i.e., the oxide film, which depends on the metal element in the bath 2 is formed.

[0071] In the bath 2, the metal element contained can be supplied to the bath 2 by dissolution of the positive electrode 6 (anode). When the metal element is dissolved from the positive electrode 6 into the bath 2, the management of the film forming rate becomes easy, and continuous and stable film formation on various substrates 5 becomes possible. When the metal element is supplied to the bath 2 by dissolution of the positive electrode 6, the positive electrode 6 preferably uses at least one electrode selected from an Al electrode, a Ti electrode, and a Mo electrode.

[0072] The metal element in the bath 2 can be supplied by a metal alkanoate and / or an inorganic metal compound. When the metal element is supplied by dissolving a metal alkanoate and / or an inorganic metal compound, it is also possible to cope with elements that are difficult to be dissolved and supplied by the positive electrode 6 (anode). In addition, in this case, multiple metal elements can be compounded to achieve film formation with controlled composition ratio.

[0073] Examples of the metal alkoxide include aluminum alkoxide, titanium alkoxide, and molybdenum alkoxide.

[0074] Examples of the aluminum alkoxide include aluminum trialkoxides, and examples of the aluminum trialkoxides include aluminum tripropoxide (e.g., aluminum triisopropoxide, aluminum tri-n-propoxide), aluminum triethoxide, and aluminum tributoxide (e.g., aluminum tri-sec-butoxide, aluminum tri-n-butoxide).

[0075] Examples of titanium alkoxides include titanium trialkoxides and titanium tetrakoxides, and preferably titanium tetrakoxides. Examples of titanium tetrakoxides include titanium tetrapropoxides (e.g., titanium tetraisopropoxides, titanium tetra-n-propoxides, etc.), titanium tetramethoxides, titanium tetraethoxides, titanium tetrabutoxides (e.g., titanium tetraisobutoxides, titanium tetra-n-butoxides, etc.), titanium tetrapentoxides, titanium tetrahexoxides, and titanium tetra(2-ethylhexoxides).

[0076] Examples of the inorganic metal compound include aluminum chloride, aluminum bromide, aluminum iodide, and titanium iodide.

[0077] When the metal element in the bath 2 is supplied by a metal alkanoate and / or an inorganic metal compound, the concentration of the metal element in the bath 2 is not particularly limited. In this case, from the viewpoint of forming a good coating 3, the concentration of the metal element in the bath 2 is preferably more than 1ppm and less than 100ppm, more preferably more than 3ppm and less than 10ppm, and further preferably more than 4ppm and less than 6ppm. It should be noted that "ppm" is "parts per million", which is "mg / L". In addition, when the bath 2 contains multiple metal elements, the concentration of the above-mentioned metal elements refers to the total concentration of multiple metal elements. The concentration of the metal element in the bath 2 can be measured by ICP-MS analysis.

[0078] (1.3) Halogen elements

[0079] The bath 2 contains at least one halogen element. The bath 2 contains a halogen element, so that the film formation is carried out at a practical speed, and the film 3 is easy to become homogeneous. The halogen element is not particularly limited. From the viewpoint of making the organic electrochemical reaction proceed rapidly and making the film 3 function as a high-quality protective film of the substrate 5, it is preferred that the halogen element is at least one selected from the group consisting of Cl (chlorine), Br (bromine) and I (iodine).

[0080] The concentration of the halogen element in the bath 2 is not particularly limited. From the viewpoint of appropriately suppressing the reaction rate, contributing to the homogeneity of the coating 3, controlling the thickness, and suppressing the peeling of the coating 3, the concentration of the halogen element is preferably 1 ppm or more and 20000 ppm or less, more preferably 5 ppm or more and 2000 ppm or less, and further preferably 10 ppm or more and 100 ppm or less. It should be noted that "ppm" is "parts per million", which is "mg / L". The concentration of the halogen element in the bath 2 can be obtained by the amount of halogen element added when the bath is established, or by ICP-MS analysis of the bath.

[0081] (1.4)Organic solvents

[0082] By making the solvent of bath 2 an organic solvent, the generation of gas in the film formation, the oxidation of substrate 5 itself are suppressed. From the viewpoint of forming film 3 well, the solvent preferably includes at least one or more selected from the group consisting of ketone and nitrile. Ketone, nitrile are included in the solvent, so as to infer that condensation reaction is caused on the electrode surface (cathode surface), and electrodeposition becomes possible. In addition, ketone is included in the solvent, so as to think that keto-enol tautomerism is produced in the presence of halogen, and the reactivity of bath 2 is improved.

[0083] (1.4.1) Ketone

[0084] The ketone is not particularly limited as long as it is an organic solvent having a carbonyl group (—C(═O)—) other than an ester bond.

[0085] Examples of ketones include acetone, methyl ethyl ketone (MEK), 1-hexanone, 2-hexanone, 4-heptanone, 2-heptanone (methyl amyl ketone), 1-octanone, 2-octanone, 1-nonanone, 2-nonanone, diisobutyl ketone, methylisobutyl ketone, acetylacetone, acetonylacetone, phenylacetone, acetophenone, methylnaphthylketone, cyclohexanone (CHN), and methylcyclohexanone. Among these, acetone and methylethylketone are preferred as ketones from the viewpoint of particularly good formation of the coating 3.

[0086] (1.4.2) Nitrile

[0087] Nitrile is an organic solvent containing a nitrile group (-CN) in its structure. Examples of nitrile include acetonitrile, propionitrile, valeronitrile, butyronitrile, etc. Among these, acetonitrile is preferred as the nitrile from the viewpoint of particularly good formation of the coating 3.

[0088] (2) Base material 5

[0089] Regarding the “substrate 5 ”, the description of the column “(1) Substrate 5 ” in the above-mentioned “1. Covering substrate 1 ” applies as it is.

[0090] (3) Voltage application

[0091] A voltage is applied while the substrate 5 is immersed in the bath 2 to form the coating 3 on the substrate 5 on the negative electrode 7 side. Specifically, the positive electrode 6 and the negative electrode 7 (substrate 5) are immersed in the bath 2 to generate a potential gradient between the electrodes.

[0092] As the positive electrode 6, any of the known conductive substrates can be used. When the metal element in the bath 2 is supplied by dissolution of the positive electrode 6, the positive electrode 6 is preferably selected from at least one of an Al electrode, a Ti electrode, and a Mo electrode. The shape, thickness, size, etc. of the positive electrode 6 are not particularly limited. The positive electrode 6 can be, for example, in the form of foil, plate, foam, nonwoven fabric, mesh, felt, or expanded metal.

[0093] The positive electrode 6 and the negative electrode 7 are preferably arranged to face each other.

[0094] The positive electrode 6 and the negative electrode 7 are connected to a DC power source, and a potential gradient can be generated between the positive electrode 6 and the negative electrode 7 by the DC power source.

[0095] To generate a potential gradient between positive electrode 6 and negative electrode 7 , a voltage (eg, a constant voltage) is applied to both electrodes from a power source connected to positive electrode 6 and negative electrode 7 while the positive electrode 6 and negative electrode 7 are immersed in bath 2 .

[0096] The potential gradient generated between the two electrodes is preferably 10 V to 300 V, more preferably 20 V to 100 V, and even more preferably 60 V to 80 V in the case of a constant voltage from the viewpoint of forming a coating at a practical speed.

[0097] The application time of the applied voltage is not particularly limited and is, for example, preferably 10 seconds to 300 seconds, more preferably 30 seconds to 240 seconds, and further preferably 60 seconds to 180 seconds.

[0098] It should be noted that the voltage may be variable rather than being a constant voltage.

[0099] (4) Treatment steps after film formation

[0100] After the film 3 is formed, the amount of carbon in the film 3 can be reduced by heat treatment and / or light irradiation. By reducing the amount of carbon in the film 3 by heat treatment and / or light irradiation, the purity of the inorganic oxide film can be controlled.

[0101] The treatment temperature of the heat treatment is not particularly limited, but is preferably 100°C to 1000°C, more preferably 300°C to 800°C, and further preferably 500°C to 600°C from the viewpoint of efficiently reducing the amount of carbon.

[0102] The treatment time of the heat treatment is not particularly limited, but from the viewpoint of efficiently reducing the amount of carbon, it is preferably from 1 minute to 60 minutes, more preferably from 5 minutes to 45 minutes, and further preferably from 10 minutes to 30 minutes.

[0103] The wavelength of light in the light irradiation is not particularly limited. From the viewpoint of efficiently reducing the amount of carbon, the wavelength of light is preferably 250 nm to 1100 nm, more preferably 300 nm to 800 nm, and further preferably 400 nm to 500 nm.

[0104] The light irradiation time is not particularly limited, but from the viewpoint of efficiently reducing the amount of carbon, it is preferably 3 seconds to 120 seconds, more preferably 5 seconds to 60 seconds, and further preferably 10 seconds to 30 seconds.

[0105] Note that the reduction in the amount of carbon in the film 3 can be confirmed by XPS analysis.

[0106] 3. Effects of the Covering Base Material 1 of the Present Embodiment

[0107] According to the present embodiment, a novel covering substrate 1 which can be used in various fields and can be mass-produced is provided.

[0108] The cover substrate 1 of the present embodiment can be formed without using an expensive raw material or by reducing the amount of the expensive raw material to an extremely small amount, and therefore is cost-effective.

[0109] Furthermore, the cover substrate 1 of the present embodiment does not need to be subjected to post-treatment such as heat treatment or light irradiation to form the coating film 3 , and thus the options for the material and shape of the substrate 5 can be expanded.

[0110] Example

[0111] The present disclosure will be described in more detail based on examples.

[0112] In addition, in the following description, the measurement conditions of XPS (X-ray photoelectron spectroscopy) are as follows.

[0113] [Measurement conditions]

[0114] X-ray beam diameter: 100μmΦ

[0115] Signal collection angle: 45.0°

[0116] Pulse energy: 140eV

[0117] Ar etching for 30 seconds (etching rate: SiO 2 Calculated as 10 nm / min)

[0118] 1. Example of supplying metal elements into the bath 2 by dissolution of the positive electrode 6

[0119] (1) Example 1 (Solvent: MEK, Positive Electrode 6: Aluminum)

[0120] use Figure 1 The film forming apparatus 11 shown in the figure. An aluminum wire is used as the positive electrode 6. A stainless steel plate is used as the negative electrode 7. The negative electrode 7 is a substrate 5 having a film 3 formed on the surface. Methyl ethyl ketone (MEK) is used as the solvent of the bath 2. In the bath 2, 600 ppm of iodine as a halogen is dissolved.

[0121] With the positive electrode 6 and the negative electrode 7 immersed in the bath 2 , 80 V was applied between the positive electrode 6 and the negative electrode 7 for 3 minutes.

[0122] The cross section of the negative electrode 7 was observed using a FIB-SEM (field emission scanning electron microscope). Figure 2 As shown, a film 3 with a thickness of 700 nm was formed on the surface of the substrate 5. Analysis was performed by XPS after Ar etching for 30 seconds, and it was found that the film 3 was aluminum oxide.

[0123] In addition, the element percentage of carbon element in the coating 3 was 5.8 atm %, and the total element percentage of aluminum element and oxygen element was 93.9 atm %.

[0124] Furthermore, the element percentage of iodine element in the coating 3 is less than 0.1 atm % (measurable lower limit).

[0125] In addition, in a cross-sectional TEM image obtained by cutting the coating 3 in the film thickness direction, no crystal grains were observed, and thus it was confirmed that the coating 3 was amorphous.

[0126] The relative density of the coating 3 was determined by the following method and the relative density was 100%.

[0127] The relative density of the coating 3 is determined by the following method. A cross-sectional TEM image is obtained by cutting along the film thickness direction of the coating 3. The area of ​​the pores is measured in a field of view of 300 nm in length and 1000 nm in width. The relative density (%) is calculated by the following formula (1). The average value of the relative density of 10 fields of view is the relative density of the coating 3. It should be noted that when the thickness of the coating 3 is less than 300 nm in length, the measurement is performed in a field of view that matches the thickness of the coating 3.

[0128] Relative density (%) = {(S1-S2) / S1} × 100 (1)

[0129] (Where S1 is the area of ​​the field of view (nm) with a vertical dimension of 300 nm and a horizontal dimension of 1000 nm 2 ), S2 is the total area of ​​pores in the field of view of 300 nm in length and 1000 nm in width (nm 2 ))

[0130] (2) Example 2 (Solvent: Acetone, Positive Electrode 6: Aluminum)

[0131] Acetone was used as the solvent of the bath 2. 14 ppm of iodine as a halogen was dissolved in the bath 2. The experiment was carried out in the same manner as in Example 1 except for the above. The cross section of the negative electrode 7 was observed by FIB-SEM, and a 130 nm coating 3 was formed on the surface of the substrate 5. XPS analysis revealed that the coating 3 was aluminum oxide.

[0132] In addition, the element percentage of carbon element in the coating 3 was 6.5 atm %, and the total element percentage of aluminum element and oxygen element was 93.3 atm %.

[0133] In addition, the element percentage of iodine element in the film 3 is 0.1 atm %.

[0134] In addition, in a cross-sectional TEM image obtained by cutting the coating 3 in the film thickness direction, no crystal grains were observed, and thus it was confirmed that the coating 3 was amorphous.

[0135] Furthermore, the relative density of the coating 3 was determined by the above method and found to be 100%.

[0136] (3) Example 3 (Solvent: MEK, Positive Electrode 6: Titanium)

[0137] Titanium wire was used as the positive electrode 6. The experiment was conducted in the same manner as in Example 1 except for the above. The cross section of the negative electrode 7 was observed by FIB-SEM, and a 90 nm film 3 was formed on the surface of the substrate 5. XPS analysis revealed that the film 3 was titanium oxide.

[0138] In addition, the element percentage of carbon element in the coating 3 was 24.6 atm %, and the total element percentage of titanium element and oxygen element was 78.7 atm %.

[0139] In addition, the element percentage of iodine element in the film 3 is 0.3 atm %.

[0140] In addition, in a cross-sectional TEM image obtained by cutting the coating 3 in the film thickness direction, no crystal grains were observed, and thus it was confirmed that the coating 3 was amorphous.

[0141] Furthermore, the relative density of the coating 3 was determined by the above method and found to be 100%.

[0142] (4) Example 4 (Solvent: Acetone, Positive Electrode 6: Titanium)

[0143] Acetone was used as the solvent of the bath 2. 2400 ppm of iodine as a halogen was dissolved in the bath 2. The experiment was conducted in the same manner as in Example 3 except for the above. The cross section of the negative electrode 7 was observed by FIB-SEM, and a 500 nm coating 3 was formed on the surface of the substrate 5. XPS analysis revealed that the coating 3 was titanium oxide.

[0144] In addition, the element percentage of carbon element in the coating 3 was 9.2 atm %, and the total element percentage of titanium element and oxygen element was 83.7 atm %.

[0145] In addition, the element percentage of iodine element in the film 3 is 0.4 atm %.

[0146] In addition, in a cross-sectional TEM image obtained by cutting the coating 3 in the film thickness direction, no crystal grains were observed, and thus it was confirmed that the coating 3 was amorphous.

[0147] Furthermore, the relative density of the coating 3 was determined by the above method and found to be 100%.

[0148] (5) Example 5 (Solvent: MEK, Positive Electrode 6: Molybdenum)

[0149] Molybdenum wire was used as the positive electrode 6. The experiment was conducted in the same manner as in Example 1 except for the above. The cross section of the negative electrode 7 was observed by FIB-SEM, and a 160 nm film 3 was formed on the surface of the substrate 5. XPS analysis revealed that the film 3 was molybdenum oxide.

[0150] In addition, the element percentage of carbon element in the coating 3 was 14.8 atm %, and the total element percentage of molybdenum element and oxygen element was 78.7 atm %.

[0151] Furthermore, the element percentage of iodine element in the coating 3 is lower than 0.1 atm % (below the detection limit).

[0152] In addition, in a cross-sectional TEM image obtained by cutting the coating 3 in the film thickness direction, no crystal grains were observed, and thus it was confirmed that the coating 3 was amorphous.

[0153] Furthermore, the relative density of the coating 3 was determined by the above method and found to be 100%.

[0154] (6) Example 6 (Solvent: Acetone, Positive Electrode 6: Molybdenum)

[0155] Acetone was used as the solvent of the bath 2. 2400 ppm of iodine as a halogen was dissolved in the bath 2. The experiment was conducted in the same manner as in Example 5 except for the above. The cross section of the negative electrode 7 was observed by FIB-SEM, and a 480 nm coating 3 was formed on the surface of the substrate 5. XPS analysis revealed that the coating 3 was molybdenum oxide.

[0156] In addition, the element percentage of carbon element in the coating 3 was 12.7 atm %, and the total element percentage of molybdenum element and oxygen element was 78.0 atm %.

[0157] Furthermore, the element percentage of iodine element in the coating 3 is lower than 0.1 atm % (below the detection limit).

[0158] In addition, in a cross-sectional TEM image obtained by cutting the coating 3 in the film thickness direction, no crystal grains were observed, and thus it was confirmed that the coating 3 was amorphous.

[0159] Furthermore, the relative density of the coating 3 was determined by the above method and found to be 100%.

[0160] (7) Example 7 (Solvent: acetonitrile, positive electrode 6: aluminum)

[0161] Acetonitrile was used as the solvent of the bath 2. 2400 ppm of iodine as a halogen was dissolved in the bath 2. In addition, the experiment was carried out in the same manner as in Example 1. The cross section of the negative electrode 7 was observed by FIB-SEM, and a 140 nm coating 3 was formed on the surface of the substrate 5. XPS analysis showed that the coating 3 was aluminum oxide. Oxygen that was not present in the bath 2 was present in the coating 3. It is presumed to be oxygen derived from water contained in the bath 2 or water absorbing moisture from the atmosphere.

[0162] In addition, the element percentage of carbon element in the coating 3 was 9.8 atm %, and the total element percentage of aluminum element and oxygen element was 90.1 atm %.

[0163] In addition, the element percentage of iodine element in the film 3 is 0.1 atm %.

[0164] In addition, in a cross-sectional TEM image obtained by cutting the coating 3 in the film thickness direction, no crystal grains were observed, and thus it was confirmed that the coating 3 was amorphous.

[0165] Furthermore, the relative density of the coating 3 was determined by the above method and found to be 100%.

[0166] 2. Example of supplying metal elements from metal alkanol to bath liquid

[0167] (1) Example 8 (Solvent: acetone, metal alkoxide: aluminum triisopropoxide)

[0168] use Figure 1 The film forming apparatus 11 shown in the figure. A carbon electrode is used as the positive electrode 6. A stainless steel plate is used as the negative electrode 7. The negative electrode 7 is a substrate 5 having a film 3 formed on the surface. Acetone is used as a solvent of the bath 2.

[0169] 16 mg / L (16 ppm) of aluminum triisopropoxide was dissolved in the bathing liquid 2 , and 2400 mg / L (2400 ppm) of iodine as a halogen was dissolved in the bathing liquid 2 .

[0170] With the positive electrode 6 and the negative electrode 7 immersed in the bath 2 , 80 V was applied between the positive electrode 6 and the negative electrode 7 for 3 minutes.

[0171] Observation of the cross section of negative electrode 7 by FIB-SEM (field emission scanning electron microscope) revealed that a 140 nm thick film 3 was formed on the surface of substrate 5. Analysis by XPS (X-ray photoelectron spectroscopy) revealed that film 3 was aluminum oxide.

[0172] In addition, the element percentage of carbon element in the coating 3 was 8.4 atm %, and the total element percentage of aluminum element and oxygen element was 84.3 atm %.

[0173] Furthermore, the element percentage of iodine element in the coating 3 is lower than 0.1 atm % (below the detection limit).

[0174] In addition, in a cross-sectional TEM image obtained by cutting the coating 3 in the film thickness direction, no crystal grains were observed, and thus it was confirmed that the coating 3 was amorphous.

[0175] Furthermore, the relative density of the coating 3 was determined by the above method and found to be 100%.

[0176] (2) Example 9 (Solvent: MEK, Metal Alkyl Alcohol: Aluminum Triisopropoxide)

[0177] Methyl ethyl ketone (MEK) was used as the solvent of the bath 2. The experiment was conducted in the same manner as in Example 8 except for the above. The cross section of the negative electrode 7 was observed by FIB-SEM, and a 300 nm film 3 was formed on the surface of the substrate 5. XPS analysis revealed that the film 3 was aluminum oxide.

[0178] In addition, the element percentage of carbon element in the coating 3 was 8.6 atm %, and the total element percentage of aluminum element and oxygen element was 83.6 atm %.

[0179] Furthermore, the element percentage of iodine element in the coating 3 is lower than 0.1 atm % (below the detection limit).

[0180] In addition, in a cross-sectional TEM image obtained by cutting the coating 3 in the film thickness direction, no crystal grains were observed, and thus it was confirmed that the coating 3 was amorphous.

[0181] Furthermore, the relative density of the coating 3 was determined by the above method and found to be 100%.

[0182] (3) Example 10 (Solvent: Acetone, Metal Alkyl Alcohol: Titanium Tetraisopropoxide)

[0183] Titanium tetraisopropoxide was used instead of aluminum triisopropoxide. Except for the above, the experiment was conducted in the same manner as in Example 8. The cross section of the negative electrode 7 was observed by FIB-SEM, and it was found that the coating 3 with a thickness of 700 nm was formed on the surface of the substrate 5 .

[0184] XPS analysis revealed that the coating 3 was titanium oxide.

[0185] In addition, the element percentage of carbon element in the coating 3 was 8.8 atm %, and the total element percentage of titanium element and oxygen element was 86.1 atm %.

[0186] In addition, the element percentage of iodine element in the film 3 was 1.3 atm %.

[0187] In addition, in a cross-sectional TEM image obtained by cutting the coating 3 in the film thickness direction, no crystal grains were observed, and thus it was confirmed that the coating 3 was amorphous.

[0188] Furthermore, the relative density of the coating 3 was determined by the above method and found to be 100%.

[0189] (4) Example 11 (Solvent: Acetone, Metal Alkyl Alcohol: Titanium Tetra-n-Propoxide)

[0190] Titanium tetra-n-propoxide was used instead of aluminum triisopropoxide. Except for this, the experiment was conducted in the same manner as in Example 8. The cross section of the negative electrode 7 was observed by FIB-SEM, and a 510 nm coating 3 was formed on the surface of the substrate 5. XPS analysis revealed that the coating 3 was titanium oxide.

[0191] In addition, the element percentage of carbon element in the coating 3 was 9.5 atm %, and the total element percentage of titanium element and oxygen element was 85.9 atm %.

[0192] In addition, the element percentage of iodine element in the film 3 is 0.9 atm %.

[0193] In addition, in a cross-sectional TEM image obtained by cutting the coating 3 in the film thickness direction, no crystal grains were observed, and thus it was confirmed that the coating 3 was amorphous.

[0194] Furthermore, the relative density of the coating 3 was determined by the above method and found to be 100%.

[0195] 3. Analysis of Film 3 by FT-IR

[0196] The coating 3 formed in Examples 1, 2, 3, and 7 was analyzed by FT-IR. The measurement conditions are as follows.

[0197] Measurement method: Single reflection ATR method

[0198] Cumulative times: 64 times

[0199] Resolution: 4cm -1

[0200] Pore ​​size: 150 μm

[0201] Any coating 3, at 3000cm -1 -2800cm -1 A peak presumed to be due to CH stretching vibration was detected.

[0202] 4. XPS-based analysis of film 3

[0203] The films 3 formed in Examples 1, 2, and 3 were analyzed by XPS. In all the films 3, C═O bonds and CO bonds were detected.

[0204] 5. Differences in film formation speed depending on the type of solvent

[0205] The relationship between electrodeposition time and deposition weight was investigated for various solvents.

[0206] use Figure 1The film forming device 11 shown. Aluminum wire is used as the positive electrode 6. A stainless steel plate is used as the negative electrode 7. The negative electrode 7 is a substrate 5 on which a coating 3 is formed. Acetone, methyl ethyl ketone (MEK), methyl isobutyl ketone, and diisobutyl ketone are used as the solvent of the bath 2. 2100 mg / L (2100 ppm) of iodine as a halogen is dissolved in the bath 2.

[0207] With the positive electrode 6 and the negative electrode 7 immersed in the bath 2 , 80 V is applied between the positive electrode 6 and the negative electrode 7 for 1 minute to 3 minutes.

[0208] For the case of using each solvent, Figure 3 The relationship between the application time (electrodeposition time) and the deposition weight (deposition mass) is shown in the figure. The deposition weight is the weight of the formed film.

[0209] Depend on Figure 3 The graph confirms that as the electrodeposition time increases, the deposition weight tends to increase. Figure 3 The graph confirms that the smaller the carbon number of the hydrocarbon group of the solvent, the faster the deposition rate.

[0210] 6. Relationship between the metal element concentration in the bath 2 and the adhesion of the film 3

[0211] The first (No. 1) sample (covering substrate 1) was prepared in the same manner as in Example 1. Sample No. 1 was pulled out from bath 2, a new stainless steel plate was placed in bath 2, and sample No. 2 was prepared in the same manner as in Example 1. Samples No. 3 and No. 4 were prepared in the same manner. When each sample was pulled out from bath 2, a portion of bath 2 was taken out and the concentration of aluminum element was measured by ICP-MS.

[0212] Figure 4 The figure shows the relationship between the number of samples produced and the concentration of aluminum in the bath 2. Figure 4 As can be seen from the graph, as the number of trials increases, the concentration of aluminum tends to increase. In addition, in sample No. 4, the coating 3 is slightly peeled off from the substrate 5. It can be seen that in order to continuously produce samples, the concentration of aluminum is preferably 1 ppm or more and 6 ppm or less.

[0213] 7. Relationship between the concentration of halogen elements in bath 2 and the adhesion of the coating

[0214] use Figure 1 The film forming apparatus 11 shown in the figure. Aluminum wire is used as the positive electrode 6. A stainless steel plate is used as the negative electrode 7. The negative electrode 7 is a substrate 5 on which a coating 3 is formed. Acetone and methyl ethyl ketone (MEK) are used as the solvent of the bath 2. Iodine as a halogen in an amount shown in Table 1 is dissolved in each bath 2.

[0215] In the state where the positive electrode 6 and the negative electrode 7 are immersed in each bath 2, 80V is applied between the positive electrode 6 and the negative electrode 7 for 3 minutes to prepare the initial (No. 1) sample (covering the substrate 1). The No. 1 sample is pulled out of the bath 2, and a new stainless steel plate is placed in the bath 2, and the same application as the No. 1 sample is applied to prepare the No. 2 sample. Similarly, the No. 3 and subsequent samples are continuously prepared.

[0216] The results are shown in Table 1. The evaluations in Table 1 are as follows.

[0217] A: The coating 3 was formed. The adhesion between the coating 3 and the substrate 5 was good.

[0218] B: The coating 3 was formed. The adhesion between the coating 3 and the substrate 5 was slightly poor, and the coating 3 was slightly peeled off.

[0219] The results in Table 1 show that the film 3 can be formed at any iodine concentration. From the viewpoint of suppressing peeling of the film 3, it was confirmed that the iodine concentration is preferably 0.001 g / L to 0.10 g / L (1 mg / L to 100 mg / L = 1 ppm to 100 ppm).

[0220] [Table 1]

[0221] Table 1

[0222]

[0223] 8. Study on the types of substrate 5

[0224] The formation of the coating 3 was attempted using various substrates 5. Permalloy plates, titanium plates, copper plates, and carbon plates were used instead of the stainless steel plates used as negative electrodes 7 in Example 1. The experiment was conducted in the same manner as in Example 1 except for the above.

[0225] Stable coating 3 was formed on any substrate 5 . It was confirmed that stable coating 3 can be formed regardless of the type of substrate 5 .

[0226] 9. Effects of the Embodiments

[0227] According to the present embodiment, a novel covering substrate 1 which can be used in various fields and can be mass-produced is provided.

[0228] The present invention is not limited to the embodiments described in detail above, and various modifications and changes can be made within the scope of the claims of the present invention.

[0229] (Note)

[0230] This specification includes the following inventions. [1]

[0232] A covering substrate, which is formed by covering the substrate with a coating film,

[0233] The thickness of the coating is greater than 1 nm and less than 800 nm.

[0234] When the film is measured by X-ray photoelectron spectroscopy, the element percentage of C (carbon) is 0.1 atm% or more and less than 20 atm%, and the total element percentage of metal elements and O (oxygen) is 70 atm% or more.

[0235] The relative density of the aforementioned coating is 90% or more,

[0236] The aforementioned coating is amorphous. [2]

[0238] The covered substrate according to [1], wherein a portion of the substrate where the coating film is formed has conductivity. [3]

[0240] The coated substrate according to [1] or [2], wherein the coating film contains a compound having at least one structure of a CH bond, a C═O bond, and a CO bond. [4]

[0242] The coated substrate according to any one of [1] to [3], wherein the element percentage of the halogen element in the coating film is 0.1 atm % or more when measured by X-ray photoelectron spectroscopy. [5]

[0244] A covering substrate according to any one of [1] to [4], wherein the metal element is at least one selected from the group consisting of Al (aluminum), Ti (titanium), Mo (molybdenum), Cr (chromium), Mn (manganese), Fe (iron), Co (cobalt), Ni (nickel), Zr (zirconium), V (vanadium), W (tungsten), Ta (tantalum), Nb (niobium) and Sn (tin).

[0245] Description of Reference Numerals

[0246] 1…Covering the substrate

[0247] 2…Bath gel

[0248] 3…Lamination

[0249] 5…Substrate

[0250] 6… Positive electrode

[0251] 7…Negative electrode

[0252] 11…Film forming device.

Claims

1. A covered substrate, which is formed by covering the substrate with a coating film, The thickness of the coating is greater than 1 nm and less than 800 nm. When the film is measured by X-ray photoelectron spectroscopy, the element percentage of C (carbon) is 0.1 atm% or more and less than 20 atm%, and the total element percentage of metal elements and O (oxygen) is 70 atm% or more. The relative density of the coating is above 90%. The coating is amorphous.

2. The covering substrate according to claim 1, wherein The portion of the substrate where the coating is formed has electrical conductivity.

3. The covering substrate according to claim 1 or claim 2, wherein: The coating film contains a compound having at least one structure of a CH bond, a C═O bond, and a CO bond.

4. The covering substrate according to claim 1 or claim 2, wherein: When the film is measured by X-ray photoelectron spectroscopy, the element percentage of the halogen element is 0.1 atm % or more.

5. The covering substrate according to claim 1 or claim 2, wherein: The metal element is at least one selected from the group consisting of Al (aluminum), Ti (titanium), Mo (molybdenum), Cr (chromium), Mn (manganese), Fe (iron), Co (cobalt), Ni (nickel), Zr (zirconium), V (vanadium), W (tungsten), Ta (tantalum), Nb (niobium) and Sn (tin).

Citation Information

Patent Citations

  • Multilayer oxide thin film element and its production

    JP1997202606A

  • Crystalline inorganic film and method of manufacturing the same, and semiconductor device

    JP2009147192A

  • CSD solution, and CIS-based film forming method using the solution

    JP2011032521A

  • Method of producing titanium oxide film, and titanium oxide film

    JP2015093821A